1986
DOI: 10.1083/jcb.103.5.1671
|View full text |Cite
|
Sign up to set email alerts
|

Transformed human cells release different fibronectin variants than do normal cells.

Abstract: Abstract. Fibronectin molecules are dimers composed of subunits whose primary structures may differ. This is due to alternative splicing in at least two regions (ED and IIICS) of the pre-mRNA.Using two monoclonal antibodies specific for two different epitopes of domain 5 (high affinity for heparin), we have quantitatively analyzed the expression of the IIICS sequence in human fibronectins from different sources. The results demonstrated that the percentage of fibronectin subunits containing the IIICS is higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 27 publications
2
49
1
2
Order By: Relevance
“…Molecular mass pattern of isolated proteins corresponded to known FN fragments, often reported as a result of in vivo or in vitro proteolytic digestion [30][31][32][33][34], and this was confirmed by the immunoreactivity with distinct mono clonal antihuman FN Abs. Thus, protein bands in the region of 50-200 kDa were identified as the main human plasma FN immunoreactive fragments and, specifically, in the high molecular mass region, anti-EDA reactivity typical of cellular FN was also detected.…”
Section: Discussionsupporting
confidence: 52%
“…Molecular mass pattern of isolated proteins corresponded to known FN fragments, often reported as a result of in vivo or in vitro proteolytic digestion [30][31][32][33][34], and this was confirmed by the immunoreactivity with distinct mono clonal antihuman FN Abs. Thus, protein bands in the region of 50-200 kDa were identified as the main human plasma FN immunoreactive fragments and, specifically, in the high molecular mass region, anti-EDA reactivity typical of cellular FN was also detected.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, we have previously demonstrated that some FN molecules are sialylated in this region (3). The 52-kD fragment also contains the last type III homology repeat (positive reaction with IST-7); this is due to the fact that this fragment originates from FN subunits in which the IIICS sequence is completely deleted, conferring to this polypeptide resistance to thermolysin (3). Because the determinant recognized by IST-9 is very sensitive to thermolysin while on the contrary, the heparin-binding domain is extremely resistant (3), we mildly digested the three purified fragments with thermolysin.…”
Section: Ricinus Communis Agglutinin Comparison Of the Nhz-mentioning
confidence: 99%
“…The characterization of the mAbs IST-2, IST-7, and IST-4 has been previously reported (3,28,33). They are specific both for plFN and cell media-cultured FN (cFN).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations